Review Artikel: Hubungan Tingkat Kepatuhan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil - Diany Aprillia Nurdimayanthi; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Iron supplements are one of the many supplements needed by pregnant women. Giving Fe tablets to pregnant women aims to reduce the incidence of anemia in pregnant women. The addition of cases of anemia in pregnant women in Indonesia continues to increase from year to year. This is due to the low compliance of pregnant women in consuming Fe tablets. In various cities in Indonesia, it is seen that the level of compliance of pregnant women in consuming Fe tablets is still low. The purpose review is to determine the relationship between the adherence of pregnant women to consume Fe tablets with the incidence of anemia in pregnant women. The type of research used is observational analysis with cross-sectional. The results from these journals show a very significant relationship between the level of compliance with anemia cases in pregnant women based on the characteristics of the respondents, such as age, education, occupation, anemia status, compliance, knowledge, attitudes, and others. To increase adherence to pregnant women, attention, counseling, and family support are needed to guarantee the health of the mother and fetus.